2022
DOI: 10.1590/0103-8478cr20210253
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary choristoma in a new-born calf with multiple cranial and nervous malformations

Abstract: Multiple congenital malformations can occur concomitantly in several species since the anomaly in one organ may lead directly to the malformation of another. Additionally, the etiology is not always clarified. Choristoma refers to an ectopic tissue that is histologically normal in an abnormal location. A case of pulmonary and nodal choristoma associated with cranioschisis, hydrocephalus, and syringomyelia in a new-born calf is reported here. Clinically, the calf had a mass in the frontal region of the head ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Os achados clínicos apresentados corroboram com a apresentação de relatos semelhantes de meningocele em bovinos, onde houve a presença de incoordenação motora, ataxia, dificuldade em se alimentar e ficar em estação, ausência de alteração em pares de nervos cranianos, além das alterações mascroscópicas, como o aumento de volume sacular, flutuante e repleto de líquido em região frontal de crânio (6,7) . Embora as anomalias congênitas sejam em geral facilmente reconhecidas com base em ampla abordagem clínica (8) , observou-se a necessidade da realização de exames de imagem para complementação e indicação de conduta cirúrgica.…”
Section: Discussionunclassified
“…Os achados clínicos apresentados corroboram com a apresentação de relatos semelhantes de meningocele em bovinos, onde houve a presença de incoordenação motora, ataxia, dificuldade em se alimentar e ficar em estação, ausência de alteração em pares de nervos cranianos, além das alterações mascroscópicas, como o aumento de volume sacular, flutuante e repleto de líquido em região frontal de crânio (6,7) . Embora as anomalias congênitas sejam em geral facilmente reconhecidas com base em ampla abordagem clínica (8) , observou-se a necessidade da realização de exames de imagem para complementação e indicação de conduta cirúrgica.…”
Section: Discussionunclassified
“…Extralobar pulmonary sequestration accounts for 14%–26% of human cases of pulmonary sequestration ( 10 , 14 ). In the veterinary literature, the congenital anomalies derived from lung tissues have been referred to by other names, including pulmonary sequestration ( 15 , 16 ), an ectopic or accessory lung ( 17 , 18 ), bronchopulmonary foregut malformation ( 19 ) and PC ( 3 , 4 , 9 , 20 ). A retrospective study using 28 bovine cases with PCs confirmed the subcutaneous involvements of these lesions in approximately 32% of animals, compared with approximately 68% of animals with intra-abdominal and intra-thoracic lesions ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the lower prevalence (14%) of the intralobar type of pulmonary sequestration accompanied with other anomalies, half of human patients with the extralobar type (PC) had various concurrent anomalies, accounting for 4% in involvements of skeletal deformities ( 14 ). Regarding congenital skeletal deformity associated with PC, two previous newborn calves had wide frontal or parietal bone defects associated with masses protruding from their head ( 3 , 16 ). Congenital vertebral abnormalities were also found in the previous bovine cases involving PCs in their backs ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations